Savage coping: Exploring deviant acts as an outlet for relieving instinctive force in Eka Kurniawan's Man Tiger - Arganingsih, Rizki; Anam, Zuhrul (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This study aims to explain the ways in which the main character's attachment to the white tiger figure can impact his personality and to describe the coping strategies that the main character employs in response to the white tiger attachment. The result of this research indicates that the main character, Margio, is depicted having deviant personalities after he believes that he possesses a white tiger inside his body. Margio’s belief in the attachment of the white tiger then led him to have deviant actions. Margio’s belief of white tiger figure can be explained by the cause of suggestion from the elders and childhood trauma he experienced from his abusive father. Margio’s deviant personalities also can be explained with coping strategies perspective. In the story, Margio portrays some coping strategies to cope with his problems. They are fantasy, denial, suppression, repression, and displacement. In conducting this study, I use psychological approaches by Sigmund Freud and coping strategies perspective. The novel Man Tiger by Eka Kurniawan is used as the primary data of this study and which was then analyzed using descriptive qualitative methods to achieve the purpose of the study. Based on the study's findings, it can be concluded that Margio, the main character of Kurniawan’s novel Man Tiger is depicted having deviant personalities. Margio’s deviant personality is caused by his belief of possessing an attachment with the white tiger figure inside his body. Moreover, Margio’s deviant personalities are also caused by the suggestion he received when he was child and his childhood trauma. In addition, the deviant actions also can be seen from coping strategies which are fantasy, denial, suppression, repression, and displacement.